2021
DOI: 10.1002/htj.22348
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of phase change material microencapsulated in a typical multilayer wall for a hot climatic zone

Abstract: A phase change material (PCM) allows releasing and absorbing energy at the phase change transition. They are employed in building walls to maintain internal thermal comfort and optimize thermal energy storage.However, the hottest cities in Morocco suffer from overheating during peak days. Consequently in this article, the purpose is to evaluate the thermal performance of incorporation of the PCM n-octadecane paraffin in a typical multilayer wall at three different locations for a Moroccan hot climate zone. Num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As detailed in references, 22,23 this property contributes to the reduction of interior temperature volatility, promoting a more stable and comfortable indoor environment. Furthermore, PCM's advantageous characteristics extend to enhancing sound insulation, as indicated by studies referenced in 24–26 . These findings underscore the multifaceted benefits of incorporating PCMs into building materials, not only for thermal efficiency but also for acoustic performance.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…As detailed in references, 22,23 this property contributes to the reduction of interior temperature volatility, promoting a more stable and comfortable indoor environment. Furthermore, PCM's advantageous characteristics extend to enhancing sound insulation, as indicated by studies referenced in 24–26 . These findings underscore the multifaceted benefits of incorporating PCMs into building materials, not only for thermal efficiency but also for acoustic performance.…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, PCM's advantageous characteristics extend to enhancing sound insulation, as indicated by studies referenced in. [24][25][26] These findings underscore the multifaceted benefits of incorporating PCMs into building materials, not only for thermal efficiency but also for acoustic performance. Improving heat transfer, microencapsulated PCMs in plasterboard resulted in a 12% cooling load reduction.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…PCM as latent storage materials can store 5–14 times more than conventional materials 8 . Several studies show the advantage of PCM in terms of additional thermal performance 9–14 . Bouzennada et al 15 investigated the thermal behavior of PCM‐filled capsules and found that adding a horizontal midseparating fin at 0° inclination angle resulted in the fastest melting and storing energy rate, reducing melting time by up to 20.52%.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of single and hybrid nanoparticles in different proportions to the PCM layer can enhance the storage capacity of the PCM layer and reduce the internal temperature amplitude by up to 18%. The hybrid nanoparticles allowed for an increase of 4°C and a phase shift of 6 hours 30 minutes compared to a conventional heated floor without PCM 11 …”
Section: Introductionmentioning
confidence: 99%